Análisis espacio-temporal de las condiciones climáticas en la zona central del Litoral ecuatoriano y su relación con el rendimiento de Tectona grandis L.f. (teca). - Llerena Garaví, Luis Eduardo (2020)
The purpose of this research project was to apply a set of spatial-temporal data analysis tools integrated into a GIS that allow researchers to recognize patterns or behaviors of activities. As a general objective, it was proposed to analyze the relationship between temperature and precipitation with the dasometric variables in teak plantations in the coastal zone of Ecuador in the period 2008-2019. From there, different goals were defined, such as determining the spatial and temporal variability of the temperature and precipitation variables in the 6 different farms that belong to the ENDESA-BOTROSA business group, said data of the variables were taken from the different meteorological stations and geoportals of NASA, CHRS and Worldclim, resulting in the farms with the highest temperature was the Yuracyacu farm and the San Pedro farm with less precipitation, with this already determined, a predictive mapping of the IMA of the teak plantations was prepared by means of the software SPSS statistic using the correlation of correlated components to determine the predictive variables that were most relevant in the study areas, such as Y, February temperature, April temperature, June temperature, July temperature, August temperature, temperature of September, October temperature, November temperature and precipitation of July which in turn were used for the linear regression model and it was defined that the variables Y (latitude), February temperature, August temperature and July precipitation were the most relevant, in addition to the ANOVA analysis of the The linear regression model specified the significance between all the predictive variables and with this the final data to be used in the final formula to quantify the projected IMA for the period 2040 - 2060 was obtained. Concluding that the most optimal sites for the growth of teak are the area of Yuracyacu and La Palma with 3.35 cm and 3.29 cm respectively. Thus, the provinces of Santo Domingo de los Tsáchilas and Los Ríos are the most suitable for this species. Key words: space-time, climatic, predictive